2011
DOI: 10.1088/0004-637x/738/2/160
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Interpretation of a Low Coronal Shock Wave Observed in the Euv by the Sdo/Aia

Abstract: Taking advantage of both the high temporal and spatial resolution of the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory (SDO), we studied a limb coronal shock wave and its associated extreme ultraviolet (EUV) wave that occurred on 2010 June 13. Our main findings are (1) the shock wave appeared clearly only in the channels centered at 193Å and 211Å as a dome-like enhancement propagating ahead of its associated semi-spherical CME bubble; (2) the density compression of the shock is 1.5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
173
1
16

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(213 citation statements)
references
References 66 publications
23
173
1
16
Order By: Relevance
“…This correlation could not be established for EIT wave speeds (Klassen et al, 2000), most likely due to the severe undersampling of the waves' kinematics. A kinematical consistency (in terms of distances/heights and speeds) between type II bursts and coronal waves was also found in a large number of case studies (e.g., Vršnak et al, 2006;Pohjolainen et al, 2008;Grechnev et al, 2011b,a;Kozarev et al, 2011;Ma et al, 2011;Kumar and Manoharan, 2013). An example is shown in the right panel of Figure 15.…”
Section: Metric Type II Radio Burstssupporting
confidence: 56%
See 2 more Smart Citations
“…This correlation could not be established for EIT wave speeds (Klassen et al, 2000), most likely due to the severe undersampling of the waves' kinematics. A kinematical consistency (in terms of distances/heights and speeds) between type II bursts and coronal waves was also found in a large number of case studies (e.g., Vršnak et al, 2006;Pohjolainen et al, 2008;Grechnev et al, 2011b,a;Kozarev et al, 2011;Ma et al, 2011;Kumar and Manoharan, 2013). An example is shown in the right panel of Figure 15.…”
Section: Metric Type II Radio Burstssupporting
confidence: 56%
“…They found that the type II burst kinematics were consistent with the wave and that the wave itself was consistent with a weak shock (Kozarev et al, 2011;Ma et al, 2011). The compression ratios derived from the band-split of the type II burst and from the EUV imaging data are actually consistent ( ≈ 1.5) and decline during the wave's propagation (Kouloumvakos et al, 2014).…”
Section: Metric Type II Radio Burstsmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent observations have provided convincing evidence that shocks can form and accelerate particles low in the corona. Ma et al (2011) suggested that the brightness enhancement ahead of the bright CME front seen by extreme ultraviolet observations of SDO/AIA is a shock signature and it forms as low as ∼1.2 R e from the center of the Sun. Gopalswamy et al (2013b) found that CME shock formation can occur substantially below ∼1.5 R e from observations of type II radio bursts produced by electrons accelerated by shocks.…”
Section: Introductionmentioning
confidence: 99%
“…As seen from Figures 2 and 3, the EUV wave appeared as bright tracks in the hotter 193, 211 and 335Å channels, while a dark track in the cooler 171Å channel, suggesting plasma heating (Wills-Davey & Thompson 1999;Liu et al 2010Liu et al , 2012Long et al 2011a;Ma et al 2011;Li et al 2012). In the 211 channel, the average propagation velocities of this EUV wave were from (448±9) to (900±10) km s −1 in the three directions.…”
Section: Observations and Data Analysismentioning
confidence: 84%